BRAIN WAVE CHARACTERIZATION OF TAFAKUR OF ISLAMIC MEDITATION ACTIVITY USING ELECTROENCEPHALOGRAM (EEG) - Habib Alasy Ariy, Mohammad
Meditation is a mind and body exercise that has many methods and is found in various cultures, spiritual traditions, and healing systems throughout the world. In Islam, there are meditation activities such as prayer, dhikr, prayers, recitations, and Tafakur. Tafakur is a spiritual activity that prioritizes contemplation/high-level thinking regarding personality, social, scientific, and spiritual matters. This research aims to determine the character of brain waves and their complexity in Tafakur activity using Power Spectral Density (PSD) and Spectral Entropy (SE) as spectral analysis. Data collection was carried out using a 5-channel emotiv insight device with a sampling frequency of 128 Hz on 15 practitioners with three categories based on activity intensity each week by applying initial rest, meditation, and final rest phases sequentially. Then, PSD analysis was carried out on delta (0.5 – 4 Hz), theta (4 – 8 Hz), alpha (8 – 13 Hz), beta (13 – 30 Hz), and gamma (30 – 45 Hz) to compare graphical patterns of normalized PSD among all phases and compare the total normalized PSD among all phases. Meanwhile, SE analysis is carried out by comparing each entropy among all phases. The results show that the normalized PSD graphic pattern for each band during Tafakur with initial rest and final rest conditions is similar. However, the total normalized PSD heatmap shows differences in the characteristics of Tafakur activities for each practitioner and is not related to the practitioner category. Through this heatmap, it is also known that the frontal channels experience bilateral activity, but the T7, T8, and Pz channels indicate different functions of parts of the brain. Meanwhile, the SE heatmap shows an increase in entropy in theta, alpha, beta, and gamma bands during Tafakur when compared to the initial rest and final rest conditions, which indicates active awareness and intensifies the information in the signal.